Digital Strategies to Enhance the Effectiveness of Learning Arabic in a Non-Native Environment - Akhmedova, A. V. (Академічні візії, 2025)
The article aims to theoretically substantiate the effectiveness of digital strategies (gamification, mobile applications, artificial intelligence) in learning Arabic in a non-language environment and to determine their potential to improve quality of students’ learning. The study’s results demonstrated the considerable potential of innovation in overcoming the main difficulties of learning Arabic in аn environment with limited linguistic immersion. It has been shown that technological solutions contribute to activating cognitive activity, increase motivation, and provide socio-emotional and cognitive support for the educational process. Personalization of learning through instant feedback based on intellectual support contributes to the formation of individual educational trajectories and compensates for the lack of a real linguistic environment. It is determined that cultural adaptation of educational content is one of the key factors in the complexity of mastering the Arabic language since digital products for the Arab-language environment are not always clear and relevant for natives of other cultures and languages.